Young people and the human-car-machine-assemblage: aesthetics, erotics and other lessons for school-based health education. Issue 6 (2nd November 2021) - Montero, Kerry; Kelly, Peter
ABSTRACT: The early twentieth-century Futurist and Fascist sense of 'speed' as an aesthetic ideal and object of desire continues to be a pervasive and powerful influence in contemporary culture. The paper explores aspects of cultural imaginaries and discourses of the body, their relationships to the motor vehicle, and how these imaginaries play out in the health education space, specifically in a schools-based road safety programme, Fit to Drive (F2D), where the erotics and aesthetics of the human-car-machine-assemblage are made absent. In imagining the limits and possibilities of human embodiment in road safety/health education, we present encounters with the fascist psyche, with Graham – a grotesque (baroque) creature at the heart of a collaborative art project/installation, with the folds of our bodies, and the competing possibilities of the baroque. Our intent is to invite a different engagement with the human-car-machine-assemblage, and to trouble what we include in, exclude from, school-based health education.